ANALISIS DAN DESAIN AICAR WASTEWATER DUMAI VARIASI TEKANAN AIR - Valentana Ardian Tarigan (Universitas Quality, 2018)
The AICAR building is part of the waste water system located in Lubuk Gaung - Dumai. Analysis and design of this AICAR uses reinforced concrete material for its structural material. Planning uses the extreme conditions of the water load / hydrostatic load variable. The selection of water load modeling becomes the key word in the analysis and design of the building mentioned above. The hydrostatic load causes the distance pattern from the pile to be limited to a minimum pile distance of 2.57 m x 3.44 m. The reinforcement on the wall has a denser distance than the floor plate reinforcement.